Optimization of an urban railway bypass. A case study in A Coruña-Lugo line, Northwest of Spain. (January 2021) - Vázquez-Méndez, Miguel E.; Casal, Gerardo; Castro, Alberte; Santamarina, Duarte
Abstract: This paper deals with a new mathematical model for designing railway bypasses. The model was developed with applications to urban areas in mind, and presents useful tools to avoid forbidden areas, buildings, and level crossings with secondary paths and other linear infrastructures. It takes into account technical constraints (minimum radii, minimum length of tangents and transition curves, maximum slopes, and also maximum azimuth changes), and ensure a suitable connection with the current layout, for both horizontal and vertical alignment. In addition, the model searches for the best bypass from an economical point of view, taking into account expropriation costs, cleaning and terrain preparation, earthwork (considering different type of materials), and railroad construction costs. This model is applied in a case study located at the Northwest of Spain, in a section of A Coruña-Lugo line, which is currently under consideration for its redesign. By using this model, a railway bypass without level crossings is obtained, avoiding the urban area of Parga and any buildings in the surrounding area, and which is optimal from an economical point of view. Highlights: A new mathematical model for designing railway bypasses is proposed. The model avoids urban areas, buildings and level crossings with secondary paths. The model gives an economically optimal bypass. The model includes the connection points as decision variables to achieve its goals. The model is successfully used in a real case study.